Non-genetic Factors affecting Body Weight and Scrotal Circumference at First Semen Collection and Semen Production Traits of Kankrej Bulls - `Dangar, Nikhil S.; Brahmkshtri, Balkrishna P.; Pandya, Gaurav M.; Deshmukh, Niteen (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted on 13 bulls of Kankrej cattle breed maintained at Dama semen station of Banas dairy (Gujarat) to studythe effects of non-genetic factors, viz., season of birth and year of birth on body weight at first semen collection (BWFSC) and scrotalcircumference at first semen collection (SCFSC) as well as the effect of BWFSC and SCFSC on future semen production traits like semenproduction period, age of bull at disposal and lifetime production of frozen semen doses per bull. The overall least squares means forbody weight of bulls and scrotal circumference of bulls at first semen collection, semen production period, age of bull at disposal andlifetime production of frozen semen doses per bull were 578.68 ± 25.18 kg, 30.86 ± 1.60 cm, 704.3 ± 151.22 days, 1875.73 ± 135.95days and 55243.83 ± 21307.60 doses, respectively. Results of the present study revealed that body weight and scrotal circumference ofbulls at first semen collection were not significantly affected by season of birth and year of birth. Similarly, BWFSC and SCFSC had nosignificant effect on semen production traits
Keywords: Age; Body weight, First semen collection; Kankrej bulls; Scrotal circumference